2010
DOI: 10.3109/00048670903393639
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive–Compulsive Disorder in Postmenopausal Women: Prevalence, Clinical Features, and Comorbidity

Abstract: OCD was not rare in postmenopausal women admitted to a gynaecology outpatient clinic. In addition, OCD appears to be frequently comorbid with depressive or other anxiety disorders in the postmenopausal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
4
12
0
Order By: Relevance
“…Our findings regarding changes in pre‐existing OCD symptoms during the premenstruum, pregnancy, postpartum, and menopause are within the range reported by previous studies . Study findings on premenstrual exacerbation of OCD report rates between 20 and 50%, whereas worsening of preexisting OCD symptoms is reported to be 8–46% in pregnancy and 29–48% postpartum .…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Our findings regarding changes in pre‐existing OCD symptoms during the premenstruum, pregnancy, postpartum, and menopause are within the range reported by previous studies . Study findings on premenstrual exacerbation of OCD report rates between 20 and 50%, whereas worsening of preexisting OCD symptoms is reported to be 8–46% in pregnancy and 29–48% postpartum .…”
Section: Discussionsupporting
confidence: 84%
“…Study findings on premenstrual exacerbation of OCD report rates between 20 and 50%, whereas worsening of preexisting OCD symptoms is reported to be 8–46% in pregnancy and 29–48% postpartum . Exacerbation of OCD symptoms at or after menopause varies from 8 to 47% . Bidirectional change (aggravation or amelioration) in OCD symptom severity during pregnancy was also found in other studies .…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Existing studies have investigated obsessions and compulsions only during and after progressive menopause with contradictory evidence (Vulink et al, 2006). One such study showed that, OCD is not a rare comorbidity during post menopause (Uguz et al, 2010), while another study demonstrated that the symptoms are more related with menarche and decreases during menopause (Guglielmi et al, 2014). …”
Section: Introductionmentioning
confidence: 99%